Disaster mitigation in an art creation approach: a case study of the dance film "Spectrumotion Coastal Flood" - Mentari Isnaini; Eko Supriyanto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The dance work for the film “Spectrumotion Coastal Flood” is an interpretation of the expressions of sentiment, habits, and ways of survival in Sayung District, Demak Regency, which are inspired by coastal flooding. This study aimed to find experimental methods and studies of dance film media. The basis for making this work are habits that have formed a new culture, such as washing feet, the way humans defecate during floods and surviving with limited activities and routines. The research method uses an empiricism approach. The production process of art creation is carried out with the stages of making an estimate of the form of the work of art as outlined in the design of the creation. The analysis was carried out by exploring knowledge about the body associated with experiments and media studies. The outcomes of this cinema dance piece are capable of evoking feelings and experiences that are appropriate for their intended purpose. Thus, the process of creating the dance film Spectrumotion Coastal Flood, which lasts 14 minutes 51 seconds, successfully presents the empirical experience of the film's dance artist